The Role of a Stoma Nurse in Addressing Specific Complications Related to Stoma Care (The Review of Diabetic Studies, 2024)
The role of a stoma nurse is pivotal in the comprehensive care of patients with stomas, particularly in addressing the specific complications that may arise following stoma creation. Stomas, which are surgically created openings for waste elimination, can significantly enhance the quality of life for individuals with conditions such as colorectal cancer or inflammatory bowel disease. However, they also present a range of potential complications, including skin irritation, stoma prolapse, stoma retraction, and psychological distress. Stoma nurses, also known as enterostomal therapists or wound, ostomy, and continence (WOC) nurses, are specially trained to manage these challenges through a combination of technical expertise and psychosocial support.This article explores the multifaceted role of stoma nurses in the preoperative and postoperative phases of care. Preoperatively, stoma nurses provide essential education to patients, preparing them for the surgical procedure and the lifestyle changes that will follow. This proactive approach helps alleviate anxiety and fosters a sense of agency among patients. Postoperatively, stoma nurses continue to play a critical role by offering hands-on training in stoma care techniques, addressing complications, and providing emotional support.The article highlights the importance of patient education in managing complications, emphasizing the need for stoma nurses to empower patients with knowledge about their stomas and the care required. Additionally, it discusses the significance of psychological support, as many patients experience emotional challenges related to their stomas. By creating a safe environment for patients to express their concerns, stoma nurses facilitate coping strategies and resilience.In conclusion, the role of stoma nurses is essential in ensuring optimal stoma care and improving the quality of life for patients. Their contributions encompass education, complication management, and emotional support, making them invaluable members of the healthcare team. Continued investment in the training and resources for stoma nurses will enhance their ability to provide comprehensive care, ultimately leading to better health outcomes for patients with stomas.